Pengaruh Budaya Organisasi dan Disiplin Kerja Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening - Heryanto, Puji; Chalimah, Chalimah (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The aim of this research is to determine and analyze the influence of organizational culture and work discipline through work motivation on employee performance at the Pekalongan City Communication and Information Service. The research method used is a quantitative method with a descriptive approach. The population in this study were 62 employees of the Dinas Komunikasi dan Informatika Kota Pekalongan. Sampling in this research used population study techniques or saturated samples, namely all employees. The data collection technique used is by obtaining data obtained from questionnaires. The statistical method used is Partial Least Square (PLS). This research data processing uses SmartPLS software version 4.0. The research results show that (1) organizational culture has a positive and significant effect on employee performance and job satisfaction; (2) work discipline has a positive and insignificant effect on employee performance; (3) organizational culture has a positive and significant effect on employee work motivation; (4) work discipline has a positive and significant effect on employee work motivation; (5) work motivation has a positive and significant effect on employee performance; (6) work motivation is able to mediate the influence of organizational culture on employee performance; and (7) work motivation is able to mediate work discipline on employee performance.